ESTIMATATION OF THE REQUIREMENT AND SUPPLY OF BALI CATTLE BREED AND BREEDING STOCK IN WEST LOMBOK REGENCY - Sudrana, I Putu (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
The  objective of this research was to estimate the number of requirement  and supply of Bali cattle breed and breeding stock in region of West Lombok Regency. A survey  was conducted at three districts sample that was divided based on high, medium, and small population of Bali cattle and also based on the condition of transportation.  There were 31 farmers as respondent and 44 heads of Bali cattle were included. Descriptive  analysis   was used to analyse the data and information. The results  showed   that the estimate number of   breed stock required for replacement was  5.60% and 4.35% for males and females calve, respectively,   and for breeding stock of males was 5.39%,  but for females was 4.22%. The estimate number of supply for breed stock of males   was 1.81%  but  for females  was -0.31%, and for  breeding stock of females was 5.87%  both based on Anonymous, (2006 and 2009) standard, but for   breeding stock  of males were -3.15% based on Anonymous, (2009) standard and 3.56% based on standard of Anonymous, (2006).